Deregulation of Regulatory T Cells in Acute-on-Chronic Liver Failure: A Rat Model - Shunlan Ni; Shanshan Li; Naibin Yang; Xinyue Tang; Shengguo Zhang; Danping Hu; Mingqin Lu (Mediators of Inflammation)
Aims. Acute-on-chronic liver failure (ACLF) and acute liver failure (ALF) are similar in many respects during their acute exacerbation; however, ACLF generally has a poorer prognosis. We aimed to investigate the role and dynamic changes of regulatory T cell (Treg) and T helper 17 (Th17) cell proportions during ACLF progress. Methods. All rats were classified into two groups randomly: ACLF group and ALF group (control group). The rat model of ACLF was preestablished by intraperitoneal injection of carbon tetrachloride for 2 months. Then acute liver injury was induced by combined D-galactosamine and lipopolysaccharide. Six time points were examined before or after acute induction. Liver samples were performed with hematoxylin-eosin and Masson staining; circulatory Treg and Th17 cell frequencies were determined using flow cytometry assays; serum levels of alanine aminotransferase, aspartate aminotransferase, interleukin-10 (IL-10), and interferon-γ (IFN-γ) were examined. Results. In group ACLF, both Th17 cell proportion and IFN-γ level presented upgrade firstly and then descend latter tendency; the trends of Treg cell proportion and IL-10 level were observed to gradually decrease and became stable. Conclusion. The Treg cells played an important role in the immunologic mechanism during the process of ACLF. And the function of Treg cells in ACLF was defective.